2013
DOI: 10.1155/2013/189129
|View full text |Cite
|
Sign up to set email alerts
|

Senescence-Related Changes in Gene Expression of Peripheral Blood Mononuclear Cells from Octo/Nonagenarians Compared to Their Offspring

Abstract: Mechanisms determining both functional rate of decline and the time of onset in aging remain elusive. Studies of the aging process especially those involving the comparison of long-lived individuals and young controls are fairly limited. Therefore, this research aims to determine the differential gene expression profile in related individuals from villages in Pahang, Malaysia. Genome-wide microarray analysis of 18 samples of peripheral blood mononuclear cells (PBMCs) from two groups: octo/nonagenarians (80–99 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Analysis of expression of genes associated with immunosenescence, such as impaired apoptosis regulation (BAK1) and cellular immune activation (CD40LG) [11], indicated no obvious impairment of the immune response in these older subjects. The elevated expression of IGFBP3 that we observed is typical of the senescence profile reported in older adults [10], and suggests that, despite characteristic cellular senescent changes in these older adults, postprandial immune activation remains unaffected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of expression of genes associated with immunosenescence, such as impaired apoptosis regulation (BAK1) and cellular immune activation (CD40LG) [11], indicated no obvious impairment of the immune response in these older subjects. The elevated expression of IGFBP3 that we observed is typical of the senescence profile reported in older adults [10], and suggests that, despite characteristic cellular senescent changes in these older adults, postprandial immune activation remains unaffected.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, oxidative stress and inflammation contribute directly to the cellular senescence that helps perpetuate the condition of immune decline in ageing [ 8 , 9 ]. Age-related differences in monocyte expression of genes has begun to establish a characteristic senescent profile in the elderly [ 10 , 11 ]. Genes, such as insulin-like growth factor-binding protein 3 (IGFBP3) [ 10 ], cluster of differentiation (CD) 40 ligand CD40LG, and BCL2 agonist/killer 1 (BAK1) [ 11 ], are involved in cellular processes’ regulative cellular function, integrity, and responsiveness, and age-related changes in expression may contribute to differences in immune responsiveness in ageing.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, it is not the Airn lncRNA per se , but rather Airn transcription what drives methylation changes and Igf2r silencing [ 45 ]. Airn is likely involved in aging and senescence through its effect on IGF2R, since senescent cells show enhanced IGF2R expression compared to proliferating cells and IGF2R is implicated in longevity [ 46 , 47 ]; however, a role for Airn in these age-related processes has not been studied directly.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, response to stress (Heat shock cognate 71 kDa protein; HSPA8), damage stimulus (X-ray repair cross-complementing protein 6; XRCC6), and chromatin remodeling (TERF1-interacting nuclear factor 2; TINF2) pathways have been shown to be downregulated in PBMC of old people. 1 Aging is associated with overactive immune cells that contribute to autoimmune diseases and downregulation of certain metabolic pathways which increase the risk of infection. This process is known as immunosenescence and is related to mitochondrial function and energy balance.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the most promising candidate genes appear to be involved in regulatory pathways such as stress resistance, immune/inflammatory response, insulin signalling, or cardiovascular function. 1 The survival and maintenance of the internal environment in many cells depend largely on their ability to respond to cellular stressors. In yeast, it has been demonstrated that Nat4 (the yeast ortholog of hNAA40) levels are mediated and controlled by caloric restriction (CR) and that one of the main effects of decreasing Nat4 levels is increasing the lifespan of yeast cells through a pathway that upregulates the host's stress-response genes, PNC1 (the yeast ortholog of nicotinamide phosphoribosyltransferase (NAMPT)), Glycogen phosphorylase (GPH1), Hexokinase (HXK), 1,4-alpha-glucan-branching enzyme (GLC3), Trehalose-phosphatase (TPS2), Glycogen [starch] synthase isoform 1 (GSY1), and Neutral trehalase (NTH1).…”
Section: Introductionmentioning
confidence: 99%